2018
DOI: 10.1115/1.4039813
|View full text |Cite|
|
Sign up to set email alerts
|

Combustion Model for a Homogeneous Turbocharged Gasoline Direct-Injection Engine

Abstract: Homogeneous charge is a preferred operation mode of gasoline direct-injection (GDI) engines. However, a limited amount of work exists in the literature for combustion models of this mode of engine operation. Current work describes a model developed to study combustion in a homogeneous charge GDI engine. The model was validated using experimental data from a 1.6 L Ford EcoBoost® engine, tested at the U.S. EPA. The combustion heat release was approximated using a double-Wiebe function, to account for the rapid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The trend observed is in agreement with the results reported by Assanis et al 32 for the ignition delays of a direct-injection diesel engine. Tolou et al 25 observed the same trend for ignition delays of a gasoline direct injection (GDI) engine. However, the former study reported an increase in ignition delays as the load further increases and exceeds 120 N m of brake torque at high-boost conditions.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The trend observed is in agreement with the results reported by Assanis et al 32 for the ignition delays of a direct-injection diesel engine. Tolou et al 25 observed the same trend for ignition delays of a gasoline direct injection (GDI) engine. However, the former study reported an increase in ignition delays as the load further increases and exceeds 120 N m of brake torque at high-boost conditions.…”
Section: Resultsmentioning
confidence: 70%
“…The most important difference lies in the treatment of heat transfer coefficients when the intake and exhaust valves are open, and intake inflow velocities and exhaust backflow velocities increase the in-cylinder heat transfer. More information can be found in the work done by Tolou et al 25 under “Numerical Approach and Model Development.”…”
Section: Numerical Approach and Model Developmentmentioning
confidence: 99%
“…In the past, various engine or engine subsystem models have been proposed by the researchers. For instance, Tolou et al have presented a semi-predictive model of a homogeneous turbocharged gasoline direct injection engine [3]. The model approximates the combustion heat release with a double-Wiebe function and predicts the cylinder peak pressure by tuning the Wiebe variables.…”
Section: Introductionmentioning
confidence: 99%